Implementation Of Sapta Pesona Values In Tourism Services In Kampung Lama Tourism Village - Ramadhan, Ikhlas; Prayogi, Budi; Lubis, Muhammad Rizki (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
This research aims to analyze the implementation of Sapta Pesona values in tourism services in the Kampung Lama Tourism Village and identify challenges and obstacles in implementing Sapta Pesona values. Research was conducted on the topic of smart villages using a qualitative approach, where the resource persons were Pokdarwis or tourism awareness groups in the Kampung Lama Tourism Village. The technique for obtaining informants in this research was carried out using a purposive sampling technique. Based on the results of the research, it can be concluded that the application of Sapta Pesona in the Kampung Lama tourist village has been implemented well, but it is still not running optimally so there is still a need for development related to the application of the 7 elements of Sapta Pesona. There are obstacles in implementing Sapta Pesona in the Kampung Lama tourist village where these obstacles come from internal Pokdarwis, local communities and the village government. This obstacle is in the form of a lack of public knowledge in waste management.